Epitope characterization of a monoclonal antibody that selectively recognizes KIR2DL1 allotypes. (9th June 2022) - Falco, Michela; Meazza, Raffaella; Alicata, Claudia; Canevali, Paolo; Muntasell, Aura; Bottino, Cristina; Moretta, Lorenzo; Pende, Daniela; Lopez‐Botet, Miguel
Abstract : Killer immunoglobulin‐like receptor ( KIR ) genes code for a family of inhibitory and activating receptors, finely tuning NK cell function. Numerous studies reported the relevance of KIR allelic polymorphism on KIR expression, ligand affinity, and strength in signal transduction. Although KIR variability, including gene copy number and allelic polymorphism, in combination with HLA class I polymorphism, impacts both KIR expression and NK cell education, only a precise phenotypic analysis can define the size of the different KIR pos NK cell subsets. In this context, reagents recognizing a limited number of KIRs is essential. In this study, we have characterized the specificity of an anti‐KIR mAb termed HP‐DM1. Testing its binding to HEK‐293T cells transfected with plasmids coding for different KIRs, we demonstrated that HP‐DM1 mAb exclusively reacts with KIR2DL1. Using site‐directed mutagenesis, we identified the four amino acids relevant for HP‐DM1 recognition: M44, S67, R68, and T70. HP‐DM1 mAb binds to a conformational epitope including M44, the residue crucial for HLA‐C K80 recognition by KIR2DL1. Based on the HP‐DM1 epitope characterization, we could extend its reactivity to all KIR2DL1 allotypes identified except for KIR2DL1*022 and, most likely, KIR2DL1*020, predicting that it does not recognize any other KIR with the only exception of KIR2DS1*013. Moreover, by identifying the residues relevant for HP‐DM1 binding, continuously updating of its reactivity will be facilitated.